A twelve‐year neonatal and pediatric high‐frequency oscillatory ventilation transport experience. Issue 5 (29th December 2020) - Piloquet, Jean‐Eudes; Genuini, Mathieu; Kessous, Katia; Maury, Isabelle; Rambaud, Jérôme; Léger, Pierre Louis; Lodé, Noëlla
Abstract: Objective: To describe the evolution over a 12‐year period of a pediatric intensive care unit transport team's (PICU‐TT) experience of pediatric and neonatal interhospital transportation on high‐frequency oscillation ventilation (HFOV). Methods: This was a monocentric retrospective observational study from January 2006 to December 2017. All patients aged under 18 years old who were transported on HFOV by the Robert Debré Hospital PICU‐TT were included. Results: Over a 12‐year period, 125 patients were transported on HFOV, including 107 newborns and 18 children. Median (range) age and weight were 9 days (1 h–9 years) and 3.3 (0.6–39) kg, respectively. Initial median oxygenation index, SpO2 /FiO2 ratio and mean airway pressure were 32, 91, and 18 cmH2 O, respectively, without significant difference between values before and after transport. Adverse events occurred during 28 transportations (22%) including three recovered cardiac arrests and one death. Overall survival rate at discharge was 74%, 78% in neonates and 56% in pediatrics, respectively. HFOV transportation rate increased over the last four years of the study for neonates and remained stable for older children. Extra‐corporeal membrane oxygenation (ECMO) initiation rate on arrival decreased and survival rate increased significantly during the last four years of the study ( p  < .05). Conclusion: This study showed the feasibility of HFOV transportation by a PICU‐TT, despite some challenges. A trend towards using ECMO more than HFOV for the most severe respiratory and/or circulatory failures was seen over the 12‐year period. The HFOV transportation rate has increased for less severe neonatal patients.